Genetic engineering of gene encoding transcription factor MtOsDREB2A form Vietnamese rice variety Chanh trui for drought stress tolerance - Quyen, Cao Le; Tu, Tran Tuan; Hoi, Pham Xuan (Academia Journal of Biology, 2012)
DREB1/CBFs and DREB2s are transcription factors belonging to the DREBP transcription factor subfamily that specifically interact with a cis- acting element, DRE/CRT, which involved in the expression of many genes responsive to drought, high-salt and cold stresses. Many DREB2 transcription factors, including DREB2A, and DREB2A CA (Arabidopsis), OsDREB2A (rice), ZmDREB2A (maize)… have been cloned and proved to play an important role in drought and high-salt stress tolerance in plant. In this study, we report the cloning, sequencing analysis and transformation of a DREB2A homolog named MtOsDREB2A from Moc tuyen rice variety (Vietnamese cultivar rice). Interestingly, MtOsDREB2A has an Open Reading Frame of 825-bp that is totally identity to Japonica rice OsDREB2A (accession numbers: NM 001048642.1; AF 300971.2; AK 067313.1; AK 121956.1). The ORF of MtOsDREB2A was cloned into the expression vector driven by ubiquitine promoter and transferred into a Vietnam highland rice variety, named Chanh trui by the Agrobacterium-mediated transfer method. As a result, from 100 Chanh trui seeds for callus formation, 25 lines transgenic rice plants were identified and PCR analysis demonstrates that 16 lines transgenic rice plants have contained the interested gene in genome.